2023
DOI: 10.1155/2023/5612061
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Brain Stimulation for Cancer Pain Management in Nonbrain Malignancy: A Meta-Analysis

Abstract: Purpose. Noninvasive brain stimulation (NIBS) has been reported to have analgesic effects on fibromyalgia and chronic neuropathic pain; however, its effects on cancer pain have yet to be determined. The present study aimed to evaluate the effects of NIBS on patients with pain secondary to nonbrain malignancy. Methods. Electronic databases including PubMed, Embase, Cochrane Library, and Web of Science were searched from inception through June 5th, 2022. Parallel, randomized, placebo-controlled studies were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The results are encouraging, with rTMS providing benefits for pain suppression in patients with cancer. This is supported by a recent meta-analysis [21] that included two of the rTMS trials [25,27]. They showed a better effect on pain with rTMS compared to CES and tDCS, but this could be attributed to the fact that tDCS and CES have been represented with only one trial.…”
Section: Conclusion Regarding Rtms In Cancer Painmentioning
confidence: 78%
See 2 more Smart Citations
“…The results are encouraging, with rTMS providing benefits for pain suppression in patients with cancer. This is supported by a recent meta-analysis [21] that included two of the rTMS trials [25,27]. They showed a better effect on pain with rTMS compared to CES and tDCS, but this could be attributed to the fact that tDCS and CES have been represented with only one trial.…”
Section: Conclusion Regarding Rtms In Cancer Painmentioning
confidence: 78%
“…All three studies had an IMMPACT recommendation score of four. None of the studies discussed below were included in the Cochrane analysis, whereas the 2023 meta-analysis by Chien [21] included Lyon's study published in 2015 [32].…”
Section: Studies Using Ces In Cancer Painmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that, in addition to implementing tDCS sessions, the literature [62][63][64] has demonstrated the effectiveness of other NIBS techniques, such as TMS, in managing pain and psychocognitive symptoms in cancer patients. In particular, it has been observed that repetitive transcranial magnetic stimulation (rTMS) significantly reduces the intensity of pain and depressive symptoms in patients with nonbrain malignancy tumors [65]. rTMS indeed has a greater and more focused electric field compared to tDCS [66].…”
Section: Discussionmentioning
confidence: 99%
“…rTMS indeed has a greater and more focused electric field compared to tDCS [66]. On the other hand, some NIBS techniques, including cranial electrical stimulation (CES), do not show a significant reduction in pain and depressive symptoms in cancer patients [65]. However, tDCS remains the more widely adopted technique due to its advantages such as simplicity and potential for remote application, thus enabling more frequent sessions [16].…”
Section: Discussionmentioning
confidence: 99%